Activation of Tag1 transposable elements in Arabidopsis dedifferentiating cells and their regulation by CHROMOMETHYLASE 3-mediated CHG methylation - Khan, Asif; Yadav, Narendra Singh; Morgenstern, Yaakov; Zemach, Assaf; Grafi, Gideon (Biochimica et biophysica acta. Gene regulatory mechanisms, 2016)
Dedifferentiation, that is, the acquisition of stem cell-like state, commonly induced by stress (e.g., protoplasting), is characterized by open chromatin conformation, a chromatin state that could lead to activation of transposable elements (TEs). Here, we studied the activation of the Arabidopsis class II TE Tag1, in which two copies, situated close to each other (near genes) on chromosome 1 are found in Landsberg erecta (Ler) but not in Columbia (Col). We first transformed protoplasts with a construct in which a truncated Tag1 (ΔTag1 non-autonomous) blocks the expression of a reporter gene AtMBD5-GFP and found a relatively high ectopic excision of ΔTag1 accompanied by expression of AtMBD5-GFP in protoplasts derived from Ler compared to Col; further increase was observed in ddm1 (decrease in DNA methylation1) protoplasts (Ler background). Ectopic excision was associated with transcription of the endogenous Tag1 and changes in histone H3 methylation at the promoter region. Focusing on the endogenous Tag1 elements we found low level of excision in Ler protoplasts, which was slightly and strongly enhanced in ddm1 and cmt3 (chromomethylase3) protoplasts, respectively, concomitantly with reduction in Tag1 gene body (GB) CHG methylation and increased Tag1 transcription; strong activation of Tag1 was also observed in cmt3 leaves. Notably, in cmt3, but not in ddm1, Tag1 elements were excised out from their original sites and transposed elsewhere in the genome. Our results suggest that dedifferentiation is associated with Tag1 activation and that CMT3 rather than DDM1 plays a central role in restraining Tag1 activation via inducing GB CHG methylation.